Amine-appended polyaniline as a water dispersible electroactive polyelectrolyte and its integration into functional self-assembled multilayers - Marmisollé, Waldemar Alejandro (2016)
We present an effective and simple method for the synthesis of poly(3-aminobenzylamine) (PABA) using a chemical oxidation strategy in aqueous solution. The polymer was characterized by NMR, LDI-TOF mass spectrometry, UV-visible, XPS and ATR-FTIR spectroscopies. Stable acidic dispersions were employed for the construction of layer-by-layer assembled films with polyanions, which effectively act as dopants of the electroactive component as revealed by spectroscopic analysis. The assembled films were electroactive in neutral solutions, probably owing to the combination of the doping effect by the polyanions and the self-doping effect of the protonated amino groups of the PABA backbone. These layers showed an electrocatalytic effect on the ascorbic acid oxidation. The advantages of employing PABA instead of polyaniline include improved electroactivity in neutral solution, good processability owing to its higher solubility in acidic solutions and increased interaction with anionic counterparts, which may propel its integration with electroactive biomolecules or conducting nanomaterials for the design of bioelectrochemical devices and energy storage applications.